Diversity and abundance of soil microbial communities decline, and community compositions change with severity of post‐logging fire. Issue 10 (14th April 2021) - Ammitzboll, Hans; Jordan, Gregory J.; Baker, Susan C.; Freeman, Jules; Bissett, Andrew
Abstract: Understanding the effects of logging and fire on forest soil communities is integral to our knowledge of forest ecology and effective resource management. The resulting changes in soil biota have substantial impacts on forest succession and associated ecosystem processes. We quantified bacterial and fungal abundance, diversity and community composition across a logging and burn severity gradient, approximately one month after fire, in temperate wet eucalypt forests in Tasmania, Australia. Using amplicon sequencing and real‐time quantitative PCR of the bacterial 16S rRNA gene and fungal ITS1 region, we demonstrate that (i) burn severity is a strong driver of soil microbial community composition, (ii) logging and high severity burning substantially reduce the biomass and diversity of soil bacteria and fungi, and (iii) the impacts of logging and burning on soil microbial communities are largely restricted to the top 10 cm of soil, with weak impacts on the subsoil. The impacts of disturbance on microbial community composition are greater than the effects of site‐to‐site edaphic differences. Fire also drives more divergence in community composition than logging alone. Key microbial taxa driving differences in severely burnt soils include bacterial genera implicated in plant‐growth promotion and producing antifungal compounds as well as saprotrophic fungi that are also capable of forming ectomycorrhizal associations. Our research suggests that low‐moderate severity burns are important for maintaining diversity and biomass in soil microbial communities but having a range of burn severities across a site contributes to the overall diversity of habitat conditions providing for both microbial and plant diversity.